The Relationship Between Self-Concept and Consumptive Behavior in Nurse Students Grade II - Derang, Imelda; Ginting, Amnita Anda Yanti; Siringo-ringo, Zaitun Martseba (GLOBAL HEALTH SCIENCE GROUP, 2024)
Consumptive behavior is a desire to buy goods without rational considerations or needs but for the sake of pleasure and popularity solely for following current fashion trends with attractive discount offers at malls, shops and online shops, therefore as a student you must train yourself to have self-esteem. positive concept, so that you are able to control yourself from various offers in the digital world. This study aims to determine the relationship between self-concept and consumptive behavior in female Nurses level II at STIKes Santa Elisabeth Medan 2023. The type of research used is quantitative with a cross-sectional research design. The population in this study amount to 71 respondents, with a total sampling technique. The instrument used is a self-concept questionnaire developed by Vivian (2016) which consists of 35 statements and consumer behavior developed by Siallagan, Derang, and Piarni (2020) which consists of 25 statements Data analysis used the chi square test, the results of the statistical test obtained a p-value of 0.005 (p <0.05) meaning that there is a relationship between self-concept and consumptive behavior in nurse students level II at STIKes Santa Elisabeth Medan 2023. The results of the study obtain a negative self-concept of 51 people (71.8%) and moderate consumptive behavior of 36 people (50.7%). Based on these results it is expected that female students to continue to improve a positive self-concept to control consumptive behavior among female students by developing useful extracurriculars by participating in UKM (Student Activity Units) such as sports, music, dance, theater, choir, etc.